GAMMA KNIFE RADIOSURGERY FOR SCHWANNOMAS IN CHILDREN AND ADOLESCENTS - Tezcanli, Evrim; Yilmaz, Meltem; Sengoz, Meric; Peker, Selcuk (OXFORD UNIV PRESS INC, 2014)
16th International Symposium on Pediatric Neuro-Oncology (ISPNO), Singapore, SINGAPORE, JUN 28-JUL 02, 2014